Resolution of Disputes Over The Regional Head Elections Post The Constitutional Court Decision Number 85/PUUXX/2022 Regarding The Implementation of Simultaneous Regional Elections in Indonesia - Ridwan Syaidi; Zainal Arifin Hoesein; Ahmad Redi (Green Publisher Indonesia, 2024)
Constitutional Court Decision Number 97/PUU-XI/2013 which in its consideration states that the Constitutional Court cannot add authority that is not contained in the 1945 Constitution, so that the Constitutional Court Decision Number 85/PUU-XX/2022 remains conditional Constitutional authority considering The Lawmakers also did not draft a special law as intended in the Constitutional Court Decision Number 97/PUU-XI/2013. The problems are (1) What are the implications of the Constitutional Court Decision No. 97/PUU-IX/2013 after the enactment of Law no. 10 of 2016 concerning the Election of Regional Heads on the Implementation of Regional Elections in Indonesia?; (2) What is the impact of resolving regional election disputes after the Constitutional Court Decision No. 85/PUU-XX/2022?; (3) What is the ideal institutional model for resolving setbacks in regional head election results? To answer this problem, a comprehensive study is needed, namely examining the 1945 Constitution, Law N0.10 of 2016, Constitutional Court Decision Number 7273/PUU-II/2004, Constitutional Court Decision Number 97/PUU-XI/ 2013, Constitutional Court Decision Number 85/PUU-XX/2022. Research Results: (1) The authority to examine and decide on the voting results of regional head elections is carried out as long as there is no special court, in order to provide legal certainty in resolving disputes over the results of simultaneous regional heads in 2024. (2) Look at the stages of regional head elections that have been advanced and have not yet been brought forward. (3) Model The ideal institution for resolving disputes over regional head election results must be a special ad hoc judicial body.